Polarization at millimeter wavelengths caused by drifting grains in protoplanetary disks - Lietzow-Sinjen, Moritz; Reißl, Stefan; Flock, Mario; Wolf, Sebastian (Astronomy and astrophysics, 2025)
Context. During the evolution of protoplanetary disks, dust grains start to grow, form larger particles, settle to the midplane, and rearrange the disk, mainly by the inward radial drift. Because of this, dust pebbles with an irregular shape usually align mechanically and thus cause polarization signatures in their thermal radiation due to dichroic emission or absorption. Aims. The goal of this paper is to evaluate the potential to trace the impact of mechanical grain alignment in protoplanetary disks on the observed degree and orientation of linear polarization at millimeter wavelengths. Methods. We combined 3D radiation hydrodynamical simulations to determine the density distribution and the velocity field of gas and dust particles, Monte Carlo dust-gas interaction simulations to calculate the mechanical alignment of dust in a gas flow, and, finally, 3D Monte Carlo polarized radiative transfer simulations to obtain synthetic polarimetric observations. Results. We find that large grains, which contribute the most to the net polarization, are potentially mechanically aligned in the protoplanetary disk under the effect of the vertical shear instability (VSI). Thereby, the drift velocity is parallel to the rotational disk axis. Assuming oblate dust grains that are aligned with their short axis parallel to the direction of the drift velocity, the resulting polarization is usually along the major axis of the disk. This is in contrast to typical drift models that propose either a radial or azimuthal drift velocity component. Conclusions. If hydrodynamical instabilities, such as the VSI, dominate the kinematics in protoplanetary disks, the mechanical alignment of dust is a promising mechanism for grain alignment in these systems. In that case, the resulting millimeter polarization allows us to trace the orientation of aligned millimeter-sized grains.